Bahasa Inggris - Nita Arrum Sari; Ketang Wiyono (Postgraduate, University of Mataram, 2025)
This study aims to develop a STEM-based e-module on dynamic fluid materials contextualized in the Perjaya Dam for grade 11 high school students. Development follows the Rowntree model, which consists of the planning, development, and evaluation stages. Formative evaluations apply the Tessmer model, including expert reviews, one-to-one evaluations, and small groups. Data was collected through guides and questionnaires. The validity of the e-modules is assessed by experts in content, design, and instruction, while its practicality is evaluated based on student responses during one-to-one and small group stages. The results show that the e-module shows a very high level of validity and is considered very practical by users. These findings show that STEM-based e-modules are suitable for use as interactive learning media. Further research is recommended to assess its effectiveness on a larger scale and for different subject matter.